2021
DOI: 10.1007/s42979-021-00615-7
|View full text |Cite
|
Sign up to set email alerts
|

Latent Fingerprint Identification System Based on a Local Combination of Minutiae Feature Points

Abstract: Latent fingerprints are the fingerprint traces obtained from various surfaces of objects found at the crime scene. Latent fingerprint quality is, therefore, poor and they suffer from non-linear distortions. This is why latent fingerprints contain partial or incomplete minutia information. Developing an automatic fingerprint identification system (AFIS) for latent fingerprints becomes a major challenge because of a small number of minutia features. Moreover, currently developed AFIS for latent fingerprints are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Table 1 highlights the important features of proposed latent fingerprint matching algorithms. It can be observed that the state-ofart matching algorithm [40][41][42]45] performs better than other listed algorithms. Table 2 provides the details of the publicly available fingerprint databases.…”
Section: Nistsd27mentioning
confidence: 97%
See 1 more Smart Citation
“…Table 1 highlights the important features of proposed latent fingerprint matching algorithms. It can be observed that the state-ofart matching algorithm [40][41][42]45] performs better than other listed algorithms. Table 2 provides the details of the publicly available fingerprint databases.…”
Section: Nistsd27mentioning
confidence: 97%
“…Miguel Angel Medina-Pérez et al [40] presented a clustering technique based on minutiae descriptors to improve MCC, M triplets, and nearby minutiae-based descriptors. The "Latent Minutiae Similarity" (LMS), "Clustered Latent Minutiae Pattern" (CLMP), and "Ratio of Minutiae Triangles" (RMT) algorithms, developed by U. U. Deshpande et al [41] , are alignment-free and rotation/scale-invariant. They clustered minutiae structures around a reference minutia and generated minutiae invariant feature vectors to develop discriminative feature vectors needed for fingerprint matching.…”
Section: Latent Fingerprint Matchingmentioning
confidence: 99%
“…Jindal & Singla (2021) used an ant colony optimization algorithm for matching the minutiae of latent fingerprints with original fingerprints. Deshpande et al (2021) presented a ratio to minutiae triangles based method which is a rotation and scale invariant approach. The presented method was used for the identification of latent fingerprints.…”
Section: Related Workmentioning
confidence: 99%